Sovereignty, science, democracy and original residual and terminal accumulation of capital - VERAZA URTUZUASTEGUI, Jorge (Utopía y Praxis Latinoamericana, 2023)
The article seeks to elucidate the importance of science and technology as the foundation of the sovereignty of the peoples, in opposition, it shows how science really subsumed under capital propitiates the dispossession of the last riches not appropriated until now by various capitals and capitalists. It shows how the democratization of science favors the sovereignty and self-determination of people. Through the concept of terminal residual original accumulation, the author makes clear its essential relationship with the submission of science to capital, and hence, its functionality to it.